PENGARUH PERTUMBUHAN LABA DAN KONSERVATISME AKUNTANSI TERHADAP KUALITAS LABA PERUSAHAAN CONSUMER NON - CYCLICALS PADA TAHUN 2018 - 2022 - Muhammad Ridwan; Adi Sofyana Latif (JURNAL ILMIAH EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2024)
The study aims to analyze the impact of Profit Growth and Accounting Conservatism on Profit Quality. The data used in the study are the annual financial reports of the consumer non-cyclicals registered in the Indonesia Stock Exchange (IDX) during the 2018 – 2022 period. Sampling taken in this study uses impressive sampling, so it obtained research samples as many as 16 companies and became 80 observation data. This type of research is quantitative and uses secondary data and through a asosiative study approach, in addition, analysis of the study uses the data regression method panel using the EViews 12 program. The variables used in this study are the Profit Growth (X1) and as the first free variables and Accounting Conservatism (X2) as both free variables and the Quality of Profit (Y) as bound variables. Research indicates that Profit Growth does not partially affect the Quality of the Profit, a partial Accounting Conservatism affects the Quality of the Profit and simultaneous Growth of the Profit and Accounting Conservatism affect the Quality of the Profit.